Pemanfaatan Media Sosial Sebagai Sistem Informasi Digital dan Promosi Potensi Wilayah - Riandy Samuel Sumolang; Wenty Zahrati; Ardiensyah Ardiensyah (BADAN PENERBIT STIEPARI PRESS, 2025)
The utilization of social media as a digital information system has become an essential aspect in supporting public services and promoting regional potential at the local government level. This study aims to evaluate the initiative of creating and managing the official social media account of the Tomohon Selatan District Office in disseminating public information and promoting tourist attractions, local culture, and community activities. The research was conducted using a descriptive qualitative approach through direct observation during an internship program. The findings indicate that social media plays a significant role in expanding the reach of information, enhancing interaction between the government and the community, and building a positive public image of the district. However, challenges such as limited digital infrastructure and lack of competent human resources in content management still need to be addressed. This study concludes that social media is a strategic tool to foster a more transparent, participatory, and adaptive local government in response to the advancement of information technology.